Genetically Similar Xanthomonas arboricola pv. pruni Strains and Associated Phages Display Phenotypic and Genotypic Variation Across 35 Years - Katherine M. D'Amico-Willman; Prasanna Joglekar; David F. Ritchie; Amber M. Smith; Helena Heiberger; Alejandra I. Huerta (Phytobiomes Journal)
Bacteriophages (phages), viruses that infect bacteria, have key ecological and evolutionary functions in the phytobiome. Despite the importance of phages as primary drivers for bacterial evolution, phage-bacteria interactions across spatiotemporal scales in natural, agricultural settings are underexplored. With increased interest in phage-based therapies to manage bacterial pathogens, an enhanced understanding of phage genetic and functional diversity at the population level and how this, in turn, impacts bacterial evolution and virulence, is necessary. This study presents data on the genetic similarity among Xanthomonas arboricola pv. pruni (Xap) strains isolated from different geographic locations that display different lytic phenotypes when challenged with a panel of six phage isolates collected in the same region over four decades. The minor yet significant genetic variation among this small population of Xap strains is structured by both geographic location and response to phage infection. Phage genomes are also highly similar, with conserved and diverse genomic loci that correspond to isolation year. The six phages characterized here cluster into the Kantovirinae subfamily and possibly form a new genus. Only future studies will elucidate the role of Xap and Xapφ phage genes identified here in the virulence and lysis of Xap and how these, in turn, impact bacterial spot disease outcomes. The research and tripartite pathosystem presented here provide a unique opportunity to investigate the coevolution of phage-phytobacterial pathogen-plant host in depth in an agricultural setting with the potential to monitor the rate at which phage populations contribute to bacterial genetic diversity across geographic and temporal scales. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.